Evaluating the Implementation of the Independent Curriculum Policy in Indonesia: Sentiment Analysis - Muhamad Sholeh; Bambang Sigit Widodo; Bima Anggana Widhiarta Putra (Studies in Learning and Teaching, 2024)
Problems still occur in the implementation of the curriculum that changed to the Independent Curriculum, which aims to give freedom to schools, teachers and students. However, in its implementation there are still problems experienced by schools. This study aims to evaluate the implementation of the Indonesian Independent Curriculum. The data used in this study came from community responses on social media and were analyzed using sentiment analysis. This research method is an ex-post evaluation of policies that have been implemented and the analysis in this study uses sentiment analysis. The results of the evaluation of the implementation of the Independent Curriculum are based on community responses. Training and mentoring options are not only carried out online but also offline to overcome the problem of proficiency in using technology. The supporting book should detail the tactical steps to implement the Independent Curriculum including the P5 project. There should be capacity building and assessment of curriculum implementation. Based on the evaluation results, there is a need for improvement in curriculum implementation, especially the communication aspect in the form of training and mentoring conducted by policy makers and the provision of guidebooks for curriculum implementation.